Sistema de gestão ambiental e benefícios para organização : estudo de caso em empresa metalúrgica do RS - Gheno, Renata (2006)
In the current context, the search for environmetal conservation has become an important tool for the companies aiming to survive in this global market. In this sense, the Environmetal Management System - EMS - allows the company to control systematically its envornmental performance and promotes a continuous operation improvement that in its operation. This is achieved through a structured process, whose pace and dimension are determined by the company itself influenced by economic circumstances. This study aimed to investigate the Environmental Management System implementation process, as well as the ISO 14001 Certification of a company belonging to the metallurgic sector in the state of RS. The methodology used was a case study, since it portrays the suitable strategy in a context in which the matters of how and why the events happen are not known or even when the researcher has little or no control over them. The review of the literature has shown that clients who have expectations on interacting with ethic organizations, especially the ones with good institutional image on the market, and which are ecologically committed, characterize the new economic context